2014
DOI: 10.1016/j.tree.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Organising evidence for environmental management decisions: a ‘4S’ hierarchy

Abstract: Making decisions informed by the best-available science is an objective for many organisations managing the environment or natural resources. Yet, available science is still not widely used in environmental policy and practice. We describe a '4S' hierarchy for organising relevant science to inform decisions. This hierarchy has already revolutionised clinical practice. It is beginning to emerge for environmental management, although all four levels need substantial development before environmental decision-make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
154
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(156 citation statements)
references
References 56 publications
1
154
0
1
Order By: Relevance
“…Dicks et al, 2014;Land et al, 2016). However, our sample of reviews suggests that many published evidence reviews are of low methodological reliability which increases the risk that they will not adequately reflect current knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dicks et al, 2014;Land et al, 2016). However, our sample of reviews suggests that many published evidence reviews are of low methodological reliability which increases the risk that they will not adequately reflect current knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…However, reviews that relate to decision-making more broadly should also aim to accurately represent the primary evidence base and report their methodology as clearly as possible. If decision-making is to be informed by evidence, it is important to ensure that this evidence is a good representation of the whole evidence base (Dicks et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A reliance on forms of evidence such as anecdotes occurs as a result of barriers to the uptake of evidence, including lack of access to scientific literature, lack of practice-relevant conservation science, time constraints, or perhaps even evidence complacency (Addison et al 2015;Walsh 2015;Sutherland and Wordley 2017). To improve the use of evidence in practice, conservation scientists have suggested that decision support tools could be better designed and utilised to deliver evidence in a useable form (Cook et al 2016;Dicks et al 2014). Indeed, conservation practitioners responsible for management and policy decisions are also calling out for user-friendly decision support tools to help incorporate evidence into decision-making (Addison et al 2017;Addison et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dicks et al 2014;Rodela et al 2017;IPBES 2016), there is a clear lack of social science research on improving design. Sustained insights from social science are needed because, as Bagstad et al (2013) argue, these tools are best designed in a collaborative manner with intended end users.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these approaches follow a logical sequence from a large volume of disparate evidence to a simple, easily understandable answer for use in policy or practice. They fall within the existing framework of the '4S' hierarchy for organising evidence described by Dicks et al (2014b). The example of natural pest regulation in agriculture was a selected case study within two entirely independent science-policy interface projects between 2012 and 2014.…”
Section: Introductionmentioning
confidence: 99%